A Study of Accounting Students' Perceptions of Gratification: A Gender Perspective Analysis - Ersyafdi, Ilham Ramadhan; Ulfah, Fitriah (Universitas Pamulang, 2025)
Students recognise that corruption is an unlawful act, harmful, and has become a critical issue in Indonesia. One of the roots of corruption is the act of gratification. In fact, the majority of students have not properly understood the concept of gratification. This study aims to comprehensively analyse accounting students' perspectives, focusing on gender differences. The study uses a questionnaire and obtains a sample of 208 students from various universities in Indonesia. The analytical method used is the independent t-test. The results of the study show that there is no difference in accounting students' views on gratification based on gender. This study is expected to contribute to educational policymakers, both at the Ministry level and at universities/higher education institutions, as a basis for making Anti-Corruption Education a mandatory general course for all students. Furthermore, it is hoped that the Ministry and universities/institutions will elaborate relevant approaches and concepts regarding corruption/gratification and collaborate with institutions/agencies that focus on corruption, such as conducting special certification for lecturers teaching Anti-Corruption Education and ensuring that the materials taught are appropriate. This will ultimately improve literacy and correct the misconceptions about corruption/gratification that have existed so far.